An An Analysis of The Relevance between The Content of The English Textbook “Headlines” for Grade XII and “Focal Point” by BSNP - Dwi Erna Finandiati; Rahayu Apriliaswati; Sumarni (CV. Eureka Murakabi Abadi, 2022)
The research is aimed to investigate the relevance between the focused materials in the English Textbook “Headlines” for grade XII and the criteria demanded by Focal Point. This research used qualitative research. This study used content analysis as the methodology. Based on the findings of analyzing the content of the textbook